Possible origin of orbital selective Mott transitions in iron-based superconductors and Ca2−xSrxRuO4 - Ze-Yi Song; Hunpyo Lee; Yu-Zhong Zhang (New Journal of Physics, 2015)
By applying dynamical mean-field theory in combination with exact diagonalization at zero temperature to a half-filled Hubbard model with two orbitals having distinct noninteracting densities of states, we show that an orbital selective Mott transition (OSMT), where part of correlated itinerant electrons become localized, will take place even if the crystal field splitting, the differences in bandwidth, and orbital degeneracy are all absent. We find that not only decoupling of charge degrees of freedom between different orbitals, but also formation of local spin triplets are crucial for the appearance of such an OSMT. The relevance of our findings to the iron-based superconductors and Ca _2− _x Sr _x RuO _4 is discussed, and a reasonable candidate to detect such an OSMT is proposed.